Surface-Alloyed Nanoporous Zinc as Reversible and Stable Anodes for High-Performance Aqueous Zinc-Ion Battery - Meng, Huan; Ran, Qing; Dai, Tian‑Yi; Shi, Hang; Zeng, Shu‑Pei; Zhu, Yong‑Fu; Wen, Zi; Zhang, Wei; Lang, Xing‑You; Zheng, Wei‑Tao; Jiang, Qing (Nano-Micro Letters, 2022)
Metallic zinc (Zn) is one of the most attractive multivalent-metal anode materials in post-lithium batteries because of its high abundance, low cost and high theoretical capacity. However, it usually suffers from large voltage polarization, low Coulombic efficiency and high propensity for dendritic failure during Zn stripping/plating, hindering the practical application in aqueous rechargeable zinc-metal batteries (AR-ZMBs). Here we demonstrate that anionic surfactant-assisted in situ surface alloying of Cu and Zn remarkably improves Zn reversibility of 3D nanoporous Zn electrodes for potential use as high-performance AR-ZMB anode materials. As a result of the zincophilic ZnxCuy alloy shell guiding uniform Zn deposition with a zero nucleation overpotential and facilitating Zn stripping via the ZnxCuy/Zn galvanic couples, the self-supported nanoporous ZnxCuy/Zn electrodes exhibit superior dendrite-free Zn stripping/plating behaviors in ambient aqueous electrolyte, with ultralow polarizations under current densities up to 50 mA cm‒2, exceptional stability for 1900 h and high Zn utilization. This enables AR-ZMB full cells constructed with nanoporous ZnxCuy/Zn anode and KzMnO2 cathode to achieve specific energy of as high as 430 Wh kg‒1 with 99.8% Coulombic efficiency, and retain 86% after long-term cycles for > 700 h. Highlights: 1 ZnxCuy alloy shell was in-situ formed on self-supported three-dimensional nanoporous Zn anode by anionic surfactant-assisted surface alloying of Zn and Cu. 2 The self-supported nanoporous ZnxCuy/Zn anodes exhibit high-rate capability, outstanding reversibility and stability during Zn stripping/plating because of zincophilic ZnxCuy to guide uniform Zn deposition and facilitate Zn stripping. 3 Aqueous Zn-ion batteries assembled with nanoporous ZnxCuy/Zn anode and KzMnO2 cathode achieve specific energy of as high as 430 Wh kg‒1 and retain 86% after long-term cycles for >700 h.